THE EXCESSIVE TECHNICAL LOSSES OF ELECTRICITY IN ELECTRICAL SYSTEMS OF POWER CONSUMPTION - KOTYSH, Andrii; SAVELENKO, Ivan; PETROVA, Kateryna (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Reducing electricity losses in electrical networks is a complex complex problem that requires significant capital investments necessary for optimizing the development of electrical networks, improving the electricity accounting system, introducing new information technologies in marketing activities and managing network modes, training personnel and equipping them with means of testing measuring devices etc. In reality, in recent years, in connection with the inclusion of normative losses in the tariff for electric energy transmission services, a dangerous trend of adapting these norms to actual losses has emerged. The article analyzes the occurrence of power losses in electrical engineering systems and electrical networks of various voltage classes. Special attention is paid to the so-called excess losses, which are not taken into account during design and operation. These losses occur in insulators, linear fittings, current-limiting reactors, electricity meters, windings of current and voltage transformers, etc. Excessive losses of electricity in electric networks are direct financial losses of electric power companies. Savings from reducing losses could be directed to technical re-equipment of networks; staff salary increase; improvement of the organization of electricity transmission and distribution; increasing the reliability and quality of electricity supply to consumers. Unaccounted losses reach approximately 1% of the total amount. This fact must be taken into account. Because currently we are talking about millions of losses.